OPTIMALISASI LINGKUNGAN PEMBELAJARAN LUAR KELAS (OUTDOOR) TERHADAP KENYAMANAN ANAK: ANALISIS KONDISI FISIK HALAMAN DI RA MUSLIMAT NU 122 SUREN II - Habibah Maulidia; Septina Zakiya Amelia Rosyada; Fadhilah Nur Aini; Cindy Novianda Mutiara Sari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The outdoor learning environment is a crucial component in the provision of quality early childhood education. This study aims to analyze the physical condition of the school yard as an outdoor learning space at RA Muslimat NU 122 Suren II, and to identify the extent to which such conditions support children’s comfort and safety during activities. The research employs a descriptive qualitative approach with observation, interview, and documentation methods. Research subjects include the school principal, teachers, and students at RA Muslimat NU 122 Suren II. The results indicate that the physical condition of the school yard generally requires optimization in several aspects, including: the completeness and safety of play equipment, the quality of yard surfaces, the availability of adequate shading, and the management of child-friendly vegetation and spatial layout. These factors significantly influence children’s comfort in conducting outdoor learning activities. This study recommends a school yard optimization program encompassing infrastructure improvements, provision of safe educational play equipment, functional vegetation planting, and teacher training in utilizing the outdoor environment as an optimal learning resource.